PEMANFAATAN INTRUSION DETECTION SYSTEM (IDS) SEBAGAI OTOMATISASI KONFIGURASI FIREWALL BERBASIS WEB SERVICE MENGGUNAKAN ARSITEKTUR REPRESENTATIONAL STATE TRANSFER (REST) - Demmy Nanda Awangga; Haruno Sajati; Yenni Astuti (Institut Teknologi Dirgantara Adisutjipto, 2013)
Many things can destabilize a computer network connections, both with regard to hardware and software. Therefore, we need a technique for network security, one of them is firewall. The problems that arise in this final project is to build a linux based firewall automation application via web service by using REST (Representational State Transfer) architecture and IDS (Intrusion Detection System). The system buid firewall rules using linux operating system with the help o f 2 pieces o f IDS to detect theactivities of traffic data between the intruder and the server that will be recorded in the IDS database. The system will compare the server with IDS on the router to get the IP address o f the actual intruders, so it will be blocked by the firewall. The applications is used to prevents the ping o f death attack usingweb service and REST protocol so that firewall rules will run automatically.